STRATEGIES FOR TEACHING STUDENTS IN GRADES 7-11 (12-18 YEARS OLD) - Mirahmedova Zilola Dilmurod kizi, Adambayeva Nafisa (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article explores effective teaching strategies for students in grades 7-11 (ages 12-18). It emphasizes the importance of aligning teaching methods with the cognitive, emotional, and social development of adolescents. Key strategies discussed include active learning, differentiated instruction, promoting critical thinking, incorporating technology, creating a positive classroom environment, and fostering self-regulated learning. These approaches aim to engage students, improve their academic performance, and support their social-emotional development. The article provides practical recommendations for educators to adapt their teaching to meet the diverse needs of students, enhancing both motivation and overall educational quality.